11+8x=3(-3+4x)

Simple and best practice solution for 11+8x=3(-3+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+8x=3(-3+4x) equation:



11+8x=3(-3+4x)
We move all terms to the left:
11+8x-(3(-3+4x))=0
We add all the numbers together, and all the variables
8x-(3(4x-3))+11=0
We calculate terms in parentheses: -(3(4x-3)), so:
3(4x-3)
We multiply parentheses
12x-9
Back to the equation:
-(12x-9)
We get rid of parentheses
8x-12x+9+11=0
We add all the numbers together, and all the variables
-4x+20=0
We move all terms containing x to the left, all other terms to the right
-4x=-20
x=-20/-4
x=+5

You can always share this solution

See similar equations:

| -6(2x+1)=3x+7-9 | | 15=h/2-11 | | -5(z+1)-3(-1-z)=-30 | | -6(2x+1)=3x+79x | | 4.9x+4.5=19.2 | | 2x+26+6=x+23 | | 9=g/2+6 | | y-22=-42 | | -x+5/2=9 | | X+8(1-x)=1 | | 4m+9=5m-8/5 | | -36=-9(6+2x) | | 8=f/2+6 | | 54+x=-78 | | 1+2r+6=3 | | y-17=-46 | | 2r/5=3r | | 6x+10/3=5 | | 5x/3+3=8 | | 5x?1=24 | | 5/6+6(x)=7(x)-2/3 | | 6n+5-10n=4n+4-7n | | 9=6x+2+7x | | 8-7y=10 | | ?14=?(?2x+2) | | 4x+(x+5)=25 | | -2(x+4)-7=-15 | | x/6/x/7=7/6 | | X÷4=90-x | | 8=n/3+7 | | 3/2d+18=1d-3 | | 12+6n=4n+6n |

Equations solver categories